고품질 무기체계 획득을 위한 성숙도평가 방안 소개 - 김현우; Hyun Woo Kim; 우순; Soon Woo; 장봉기; Bong Ki Jang (品質經營學會誌, 2013)
Purpose: Technology readiness assessment(TRA) used as a standard readiness assessment tool in the acquisilion program of weapon system has some limitations in the comprehensive understanding of the complex system. Therefore, this research is intended to suggest a holistic maturity assessment method for the acquisition of high quality weapon system. Methods: Technology readiness level(TRL), manufacturing readiness Jevel(MRL). integration readiness level(IRL) and system readiness level(SRL) developed to assess system maturities in the various aspects are compared and analyzed to draw an improvement avenue for the current readiness assessment method. Results: TRL. MRL, IRL and SRL have large differences in their maturity targets during the acquisition life cycle: technological performance, manufacturing capability, interface between components and total system. respectively. They complement one another`s shortcomings Conclusion: To achieve a successful acquisition of high quality weapon system, multi-dimensional readiness assessment is required. Therefore. comprehensive readiness assessment using TRL, MRL, IRL and SRL will contribute to the acquisition of high quality weapon system through the accurate maturity information of overall system.